Inclusive education: psychological process and the occupational therapy - Ghirardi, Maria Isabel Garcez (Revista de Terapia Ocupacional da Universidade de São Paulo, 2000)
This text, presented at the VI Brazilian Congress ofOccupational Therapy, aimed at discussing present practices related to social inclusion of disabled persons. We have focused specifícally on practices conceming the professional role of such population.